The Effect Of Service Quality And Location On Customer Satisfaction Of Warkop Papa Pangkalpinang - Syafrullah Syafrullah; M Makrus (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to determine the effect of service quality and location on customer satisfaction at warkop Papa Pangkalpinang. This type of research is an explanatory research with a quantitative approach and uses a survey method conducted on 100 customers of Pangkalpinang Warkop Papa. Sampling used nonprobability sampling method with purposive sampling technique. Data processing is done by using several linear regression analysis tools. Based on hypothesis testing, t test results show that promotion and service quality have a significant simultaneous effect on customer satisfaction.